THE STRUGGLE OF ROCKY TO SURVIVE IN DON'T BREATHE MOVIE DIRECTED BY FEDE ALVAREZ - Indriyani, Furi; Mardewi, Tati; Wardani, Sharaswati (English Education:Journal of English Teaching and Research, 2020)
The purpose of this study was to determine the struggle of the main character namely Rocky in Don't Breathe Movie. The writer uses the descriptive qualitative method in analyzing the struggles of the main characters in Don't Breathe Movie written by Fede Álvarez to make paper arrangements correctly. The procedures that the writer takes to get the best results are observing and understanding the movie, collecting data consisting of struggles, choosing theories to analyze data, analyzing data using theories, making conclusions from the analysis, and finally compiling the final project. The results of this study are the writer finds three types of struggle namely; struggle for life, struggle for love and, internal struggle. The struggle of life when the main character in the movie survives with full force in any situation, the struggle of love when the character in the movie has a feeling of love with other characters, the internal struggle when the character in the movie has desires and problems in her life. This movie teaches humans about how important the struggle in life and make a better change, never give up and despair. The main character shows people that a struggle can be motivated by certain aspects. Keyword: Struggle, Main Character, Struggle of Life, Struggle of Love, Internal Struggle.